1992
DOI: 10.1111/j.1651-2227.1992.tb12238.x
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal N‐acetylcysteine use in infants with chronic lung disease

Abstract: To evaluate the effect of intratracheal administration of N-acetylcysteine (Mucomyst) on the clinical status, pulmonary function and gas exchange in premature infants with chronic lung disease, we conducted a randomized, placebo-controlled, crossover trial. Ten mechanically ventilated infants (gestational age 27 +/- 1 week; postnatal age 22 +/- 6 days) with clinical and radiological evidence of chronic lung disease and increased airway secretion were enrolled in the study. Each infant received tracheal adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…In a randomised, placebo, cross-over trial of intratracheal N-acetylcysteine, 2 of the 10 premature infants with BPD had increased airway resistance and frequency of cyanotic spells and bradycardia when given N-acetylcysteine 48. The current data do not support the use of mucolytic agents in intubated infants.…”
Section: Mucolyticscontrasting
confidence: 72%
“…In a randomised, placebo, cross-over trial of intratracheal N-acetylcysteine, 2 of the 10 premature infants with BPD had increased airway resistance and frequency of cyanotic spells and bradycardia when given N-acetylcysteine 48. The current data do not support the use of mucolytic agents in intubated infants.…”
Section: Mucolyticscontrasting
confidence: 72%
“…We also observed that intratracheal administration of NAC together with BPEx, unexpectedly, was toxic or pro-inflammatory to the animals. Delivery of NAC into the airways has been reported to have the potential to induce bronchospasm and irritant effects (43,44) and i.p. administration is far more common.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, N-acetylcysteine delivered intratracheally to 10 mechanically ventilated infants (gestational age=271 week; postnatal age=226 days) with BPD, led to an increase in airway resistance and the number of cyanotic spells without an appreciable effect on mucous viscosity. 19 In contrast, the combination of bronchoscopy plus N-acetylcysteine in a patient with severe asthma resulted in effective airway clearance and reduced airflow obstruction. 20 Both N-acetylcysteine and 2-mercaptoethane sulfonic acid work by breaking covalent bonds of the mucous through opening the disulfide connections.…”
Section: Discussionmentioning
confidence: 99%